Pojęcie umowy mieszanej: [The notion of mixed contract] (Studia Prawnicze / The Legal Studies, 2010)
Problem umów mieszanych próbuje się w naszej literaturze wyeliminować. Kroki takie podejmowano zarówno w przeszłości, jak i obecnie. W zeszłorocznym wydaniu „Studiów Prawa Prywatnego” Zeszyt 1 (12) 2009 Wojciech J. Kat-ner zaprezentował artykuł zatytułowany „Pojęcie umowy nienazwanej”, będący zapowiedzią publikacji wydanego w maju 2010 r. tomu 9 Systemu Prawa Prywatnego. Prawo zobowiązań – umowy nienazwane. Podjęcie tego tematu przez wybitnego przedstawiciela doktryny, a jednocześnie praktyka należy uznać za niezwykle cenną i potrzebną inicjatywę. Zagadnienie to bowiem wzbudza w naszej doktrynie sporo kontrowersji. Od lat prowadzone są dyskusje, czy istnieje potrzeba utrzymania samodzielnej kategorii umów mieszanych, czy też należy traktować je jako podgrupę umów nienazwanych. Umowy pozakodeksowe – jak pisze Wojciech J. Katner – mają często charakter mieszany, co występuje w konstrukcji wielu umów nienazwanych. Nie jest on zwolennikiem postrzegania w umowach mieszanych trzeciej kategorii umów, obok nazwanych i nienazwanych. Będą to z istoty swej umowy nienazwane. Dalej stwierdza natomiast, przytaczając argumenty podnoszone wcześniej w pracach Z. Radwańskiego i B. Gawlika (nie podając innych), że tak z teoretycznego, jak i praktycznego punktu widzenia, objawiającego się większą klarownością, nie powodując przy tym rozbicia „jedności prawnej i funkcjonalnej umownego stosunku prawnego”, lepiej jest nie wyróżniać trzeciego rodzaju umów jako mieszanych. Najlepiej, jeśli znajdą się one w gronie umów nienazwanych. The issue of mixed contracts in Polish doctrine of civil law returns every now and then. It certainly requires proper solution and proves that attempts at rejecting it as an independent category have not brought us any nearer to solving the problem. For ages, since the Roman times mixed contracts have been the subject matter of thorough analyses and interesting solutions. Also in Polish legal literature the necessity of distinguishing an independent category of mixed contracts has been repeatedly emphasised (see Chapter 2, item 3). Also, many years ago this issue was stressed by M. Sośniak, whose timeless studies were invaluable help when writing this dissertation. A dichotomic division into nominate and innominate contracts imposed on Polish doctrine turned out to be insufficient. This is proved both by the complicated nature of contemporary contractual relations, which are too difficult to be confined within rigid forms regulated by codes and other acts in the form of nominate contracts, and by caselaw. In the Fascicle 1 (12) 2009 ”Studies in Private Law” issued in 2009 Wojciech J. Katner presented an article entitled ”The notion of innominate contract” forerunning the publication of the issued in May 2010 Volume 9 Private Law System. Contract Law – innominate contracts. Raising this issue was an important and necessary initiative both in terms of classification of contracts, as well as their occurrence apart from mixed contracts. However, the omission of an independent category of mixed contracts in Volume 9 Private Law System, especially for the reason of the reputation of the previous issues, gives rise to disregarding the vast theoretical output related to this category of contracts. Instead of using the output – it is rejected as useless. According to the author of this publication, negating an independent category of mixed contracts was a result of taking within the last forty years false assumptions based on the premises of correctness of logical division without paying more attention to the doctrine analysis. Therefore, in the dissertation there are presented the opinions of both the most prominent Polish civil law scholars supporting the maintenance of the independent category of mixed contracts and the scholars with enormous scientific output, opposing this independence. No one doubts the fact that mixed contracts do not manifest full constructive novelty, which constitutes a distinctive feature of innominate contracts. Mixed contracts are more or less a coherent blend of the previously appearing contract elements. The point is this blend should be so coherent (as opposed to nexus of contracts) that it could justify the existence of a separate, independent contract. For a contract to be considered innominate its provisions must contain new original elements which do not appear in any type of nominate contracts. However, what is conditional of considering a contract to be a mixed contract is a combination of content elements of nominate and innominate contracts. These issues were discussed in detail in this dissertation. Apart from that, mixed contracts constitute only a part of the whole system of untypical contracts. Attributing one name of innominate contracts to the whole system of untypical contracts does not bring us any nearer to the development of methods of determining their legal regime. The issue raised in the dissertation aims at outlining the extensive theoretical output connected with this category of contracts as well as indicating how it can be used when classifying such contracts and when the parties have not given the contract suitable features which will allow to classify it as a nominate contract of a certain type and when and on the basis of which features, one can classify it as either mixed or innominate contract with different consequences of that.